The Relationship Between Science Literacy and Critical Thinking Skills Among Students at Public Senior High Schools in Bone Regency - Andi Nurhidayah; Eda Lolo Allo; Halimah Husain (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the relationship between students’ science literacy and critical thinking skills regarding buffer solutions. This study employs a quantitative approach using a correlational method analyzed through simple linear regression. The study population consists of all students at State Senior High Schools in Bone Regency, with samples randomly selected from one class at each school. The instruments used include a science literacy test based on PISA indicators and a critical thinking skills assessment based on Ennis’s indicators. Data were analyzed using classical assumption tests, followed by Spearman’s rank correlation and regression analysis.  The results of the data analysis using the Spearman rank test showed a correlation coefficient of 0.882 with a significance value of 0.000 < α = 0.05. Meanwhile, the results of the linear regression test yielded a correlation coefficient of 0.901 with a significance value of 0.000 < α = 0.05. These results indicate that there is a significant relationship between students’ science literacy and their critical thinking skills. Science literacy makes a positive contribution to the improvement of critical thinking skills; thus, the higher the students’ science literacy, the better their critical thinking skills.